(untitled) - Chapman, Keith (Cambridge, Mass., USA, 1991)
The petrochemical industry occupies a crucial place in the 20th century, in economic, strategic and political terms. This book charts its history from its origins in the 1920s to the present. It represents the results of 20 years of research and reflects the author's privileged access to company sources both in the United States and in Europe. The author shows the importance of product-innovation (in, for example, plastics, rubber, fibres, detergents and solvents) and process-refinement which led to the expediential growth of the industry in the Untied States, Europe and Japan from the mid 1930s to the late 1970s. The author then describes and analyses the international, national and regional response of the industry over the last 15 years to overcapacity on the one hand and to a succession of crises in oil production, notably in the Middle East. The geographical coverage of the book extends from the regional to the international scale and its historical scope embraces one hundred years from the laboratory origins of polymer science and petrochemistry to the massive operations of the modern petrochemical industries. Dr Chapman also shows how innovation and patterns of technical change have influenced and themselves been changed by geopolitical factors from two world wars to the drive for import substitution in the Third World.
Keywords: Công nghệ hóa dầu,Petroleum chemicals industry